Irrational Exuberance for Market-based Reform: How Federal Turnaround Policies Thwart Democratic Schooling. Issue 6 (June 2015) - Trujillo, Tina; RenÉE, Michelle
Background: In 2009, the Obama Administration announced its intention to rapidly "turn around" 5, 000 of the nation's lowest-performing schools. To do so, it relied on the School Improvement Grant (SIG) program to provide temporary funding for states and schools, and to mandate drastic, school-level reforms. Most of these reforms require massive administrative and teacher layoffs, especially under the "turnaround option."In the public debate about the SIG program, reforms such as turnarounds have been described as new and innovative. In reality, the nation has significant experience with them, particularly over the past 40 years. Turnaround-style reforms are not only based on unwarranted claims; they ignore contrary research evidence about the potential of mass firings to improve organizational performance. Purpose: This paper considers the tensions with democratic education inherent in the federal SIG program's market-based school reforms. It examines the evolution of and intent behind the 2009 federal SIG program. From there, it considers the lessons of forty years of research on educational effectiveness and high-stakes accountability. It builds on this evidence, as well as the growing literature on communities' engagement in reform, in its analysis of the school turnaround research and practice. The paper culminates in a set of recommendations that are intended to re-center the purposes of public education for low-income students, students of color, and local communities in developing more equitable, democratic school turnarounds. Research Design: This article synthesizes forty years of research on school and district effectiveness, high-stakes accountability, and community engagement in school reform to evaluate the federal School Improvement Grant program's potential to cultivate democratic, equitable public schools. It also reviews the small, but rapidly growing literature on school turnarounds, paying particular attention to the ways in which this new field reproduces or departs from earlier literature that examined reform models that are analogous to the current SIG-funded school turnarounds. Conclusions: Based on the provisional lessons that are emerging from current SIG-inspired turnarounds, from research on earlier efforts to improve school and district effectiveness, and from pockets of promising community-based practices that are developing at local and national levels, we propose five steps that federal, state, and local policymakers can take toward fostering more equitable, democratic turnaround processes. First, increase current federal and state spending for public education, particularly as it is allocated for more democratic turnarounds. Second, focus turnaround policies on improving the quality of teaching and learning rather than on technical-structural changes. Third, engage a broad cross-section of schools' communities—teachers, students, parents, and community organizations—in planning and implementing turnaround strategies that are tailored to each school and district context. Fourth, incorporate multiple indicators of effectiveness—apart from test scores—that reflect the range of purposes for schools. Fifth, support ongoing, systematic research, evaluation, and dissemination examining all aspects of turnaround processes in schools and districts.